Sports resources to protect youth from criminal at the center of Ninava sate as perceived by authority of the sports organizations - Naif , Abd alaziz; Mohammed , Jassim (Journal of Physical Education, 2012)
The research aimed at being acquainted with the most effective Sports resources to protect youth from criminal at the center of Ninava sate as perceived by authority of the sports organizations generally and separately.The society of the research included the authority of 46 subjects representing the sports organizations at Ninava sate. The sample was 42 subjects chosen intently from presidents of sport federations at Olympic committee, presidents of sport clubs of the state, and directors of the youth clubs at the Ninava directory of the sport and youth in addition to the dean of sport education college, the director of the collegiate sports unit at university of Mosul, and the director of the sports activities at directory of Ninavah education. As a society percentage, the sample was 91.30 %.The interview and questionnaire were used as instruments to collect data. The scientific processes were used for the final questionnaire. The arithmetic mean, standard deviation, one sample “t” test, Person correlation coefficient, Spearman-brown equation , percentage, test mean, ANOVA and Post Hoc Duncan multiple comparisons were used to process data statistically.The research concluded very important findings and as the following: The effective Sports resources to protect youth from criminal at the center of Ninava sate as perceived by authority of the sports organizations generally and separately were grouped in the following Aspects respectively via the significance of their arithmetic means against the test mean: the obligation of religious, ethic and athletic values; conducting athletic competitions, seminars and conferences; availability of athletic facilities; availability of the family, media and financial support ; conducting the athletic school and collegiate activities; and the obligation of rules and Law.